The Volatile Components Obtained from Some Oolong Tea Products - Cung, Thi To Quynh; Phan, Thi Thanh Hai; Vu, Hong Son (Old Journal, 2019)
Oolong is a traditional Chinese tea produced through a process including withering the tea leaves and oxidation before curling and twisting. There are some varieties of tea products with different flavours based on the degree of oxidation. In this study, the volatile components from 6 types of oolong tea products were obtained by hydro-distillation using Clevenger type apparatus combined with solvent extraction method, analyzed by GC-MS, and then compared to those obtained by SPME method. These results showed that the main volatile components of these studied tea products were (Z)-linalool oxide, (E)-linalool oxide, linalool, epoxylinalol, 3,7-dimethyl-1,5,7-octatrien-3-ol, (E)-geraniol, nerolidol, (Z)-2-penten-1-ol, furfural, phytol... These oolong tea products were also classified into 3 groups based on the volatile composition in the essential oil obtained by hydro-distillation.